Pengaruh Konsumsi Sarapan Terhadap Konsentrasi Belajar Mahasiswa Pendidikan Biologi Angkatan 2025 UIN Walisongo Semarang - Alifiya Ilmal Khasna; Nila Puspita Aryani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Breakfast is an important source of energy that supports brain function and learning concentration. However, many university students still skip breakfast due to busy schedules and lack of awareness regarding its importance. This study aimed to determine the effect of breakfast habits on the learning concentration of Biology Education students batch 2025 an UIN Walisongo Semarang. This research used a quantitative correlational approach with 74 respondents selected through simple random sampling. Data were collected using questionnaires related to breakfast habits and learning concentration. The data were analyzed using Pearson correlation and simple linear regression tests. The results showed that breakfast habits had a positive and significant effect on students’ learning concentration, with a Pearson correlation value of 0.519 and a significance value of < 0.001. The regression analysis indicated that breakfast habits contributed 26.9% to learning concentration, while the remaining percentage was influenced by other factors. Students who regularly consumed breakfast tended to have better concentration during lectures compared to those who rarely or never had breakfast. These findings indicate that breakfast plays an important role in supporting students’ academic readiness and learning performance. Therefore, students are encouraged to maintain regular and healthy breakfast habits to improve their concentration and academic achievement.